Evaluation of the early detection program for cervical cancer using the see-and-treat method - Dewi, Candra Ratna; Palimbo, Adriana; Mahdiyah, Dede (Health Sciences International Journal, 2024)
Background: Cervical cancer is the second most common type of cancer among women in Indonesia after breast cancer and is the third leading cause of cancer death. Objective: Evaluating the implementation of the early detection program for cervical cancer using the see-and-treat method at Martapura 2 Community Health Center. Method: The research design uses quantitative descriptive methods. Sampling used random sampling techniques and obtained 23 health workers as respondents. Data collection was carried out using a checklist sheet. Data were analyzed using univariate analysis. Results: The results of the study showed that all respondents (100%) stated that they had carried out coordination, had not provided training to cadres (100%), Health Workers who had attended training in early detection of cervical cancer (13%), had provided education to the community about cervical cancer (87%), and counseling about the HPV vaccine (61%), there were no problems during the VIA examination (78%), the completeness of the cryotherapy examination equipment met the standards (100%), there were no problems during the implementation of cryotherapy (100%), supported the procurement of the HPV vaccine (96%), but only (22%) proposed the procurement of the vaccine, the majority of respondents stated that patients with IVA results with extensive lesions > 75% were willing to be referred (87%), and stated that there were no obstacles in the referral system (91%). Conclusion: Implementing the early detection program for cervical cancer using the see-and-treat method at Martapura 2 Community Health Center needs improvement.